The Politics of Allyship with Indigenous Peoples in the Canadian Refugee-Serving Sector - Nobe-Ghelani, Chizuru; Lumor, Mbalu (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2022)
What does it mean for the refugee-serving sector to be an ally to Indigenous Peoples? This is the entry point to our reflexive journey on Indigenous–refugee relations. In this conceptually orientated article, the authors seek to consider decolonizing in the refugee-serving sector in the context of settler colonial Canada. The article examines the politics of the refugee-serving sector and argue that for it to meaningfully establish with Indigenous people, we must continue to the whiteness that has constructed and organized our sector. The authors highlight the tensions that exist in between Indigenous and refugee communities and discuss ways to work with those tensions. Three concrete approaches are suggested that may lead to decolonizing in the refugee-serving sector: critical reflexivity, settler responsibility, and renewing relationships with local Indigenous communities and lands.